Effect of cimetidine on the amounts of histamine in the gastric mucosa of patients with gastric or duodenal ulcers. Issue 11 (November 1981) - Man, W K; Saunders, J H; Ingoldby, C; Spencer, J
Abstract : Measurements were made of the amounts of histamine extracted from patients with peptic ulcer disease and control subjects suffering from various gastrointestinal diseases. Patients with duodenal ulcer, gastric ulcer, or recurrent duodenal ulcer after proximal gastric vagotomy often had less gastric mucosal histamine than did normal controls. Cimetidine therapy increased the amounts of the histamine to above control levels, presumably by suppression of output. It is concluded that endogenous amounts of histamine reflect the pathogenic states in the gastric mucosa of patients with peptic ulcer diseases. Cimetidine, as does vagotomy, increases the amount of gastric mucosal histamine. These findings suggest that the increase in mucosal histamine with cimetidine is not due to activation of histamine methyl transferase, but rather to suppression of histamine output into the gastric juice.